Pengaruh Model Latihan Smash Menggunakan Lambungan Setter dan Lemparan Bola terhadap Peningkatan Kemampuan Smash pada Atlet Prajunior Diklat Bola Voli Kudus Tahun 2022 - Savira, Shania Nur; Wahyudi, Agung (Universitas Negeri Semarang, 2023)
Volleyball is a type of sport played by 2 opposing teams where 1 team consists of 12-14 players with 6 core players and the rest are reserve players. This type of research is quantitative by experimental methods. The research design is a two-group pretest-postest design. The subject is a prejunior athlete of the Kudus volleyball training. The sampling technique is total sampling and grouping of samples by ordinal pairing patterns A-B-B-A. Data analysis using normality test, homogeneity test and hypothesis test: paired sample t test. Based on the paired sample t test, a sig (2-tailed) value of 0.000 < 0.05 was obtained, meaning that there is an influence of the smash training model using the setter hull and ball throwing in improving smash ability in prejunior athletes of the Kudus volleyball training in 2022 and there are differences in the smash training model using the setter hull and ball throwing on the improvement of smash ability in prejunior athletes of the Kudus volleyball training in 2022. Then the mean difference value of -3,500 means that the smash training model using ball throwing is more effective than using a setter.